Organizational communication as an effort to improve managerial performance, quality of work-life and job satisfaction - Irfandi Buamonabot; Adnan Rajak; Zulkifli Zulkifli (International Journal of Communication and Society, 2023)
This study's goal was to test performance variables for mediating the relationship between quality work-life (QWL) and job satisfaction. The population in this study was the entire village government in North Halmahera Regency. The purposive sampling technique was used because only the position of village head amounted to 121 respondents. The data was collected through surveys with questionnaires. The questionnaire instrument test used a validity test that is a factor analysis with a loading factor value of ≥ 0.5, and a reliability test with a Cronbach alpha value of ≥ 0.7. Hypothesis testing used regression and hierarchical regression. The result shows the following findings: both job satisfaction and managerial performance is affected by QWL positively and significantly; job satisfaction is positively and significantly influenced by managerial performance; and managerial performance can act as mediating variable on the relationship between QWL and job satisfaction. In conclusion, this study still has several limitations, especially regarding job satisfaction variables. Therefore, further research is suggested to investigate the implications of both the intrinsic and extrinsic job satisfaction on the quality of life variables.